Serotype Distribution and Antimicrobial Resistance Profile of Haemophilus influenzae Isolated from School Children with Acute Otitis Media - Dodi Safari; Daniel Joko Wahyono; Wisnu Tafroji; Anton Budhi Darmawan; Yayah Winarti; Wahyu Dwi Kusdaryanto; Wisiva Tofriska Paramaiswari; Hendro Pramono; Meyta Pratiwi; Muhamad Riza Chamadi (International Journal of Microbiology)
Haemophilus influenzae is a Gram-negative opportunistic bacterial pathogen of the human respiratory tract. This study describes the prevalence, serotype distribution, and susceptibility profiles of H. influenzae strains isolated from the nasopharynx of school children with acute otitis media (AOM) in Banyumas Regency, Central Java, Indonesia. H. influenzae was isolated from nasopharyngeal swab specimens using chocolate agar plates supplemented with IsoVitaleX and bacitracin. Serotyping was performed using quantitative polymerase chain reaction. Antimicrobial susceptibility profiles were determined using a microdilution broth assay. H. influenzae was present in 69.7% of samples (85/122). Nontypeable H. influenzae (NHTi) was the most common serotype (95.3%), followed by H. influenzae type b (3.5%) and H. influenzae type f (1.2%). All the H. influenzae isolates were susceptible to levofloxacin, ceftriaxone, imipenem, meropenem, cefuroxime, and cefixime. Most isolates were susceptible to sparfloxacin (99%), cefepime (99%), amoxicillin/clavulanic acid 2 : 1 (99%), ampicillin/sulbactam 2 : 1 (96%), chloramphenicol (94%), tetracycline (93%), ampicillin (87%), and clarithromycin (82%). Nineteen percent of the isolates were resistant to cotrimoxazole, and 11% of the isolates were resistant to ampicillin. This study showed that H. influenzae carriage among samples was dominated by NTHi and less susceptible to cotrimoxazole.